PENDAMPINGAN UMKM DALAM PENGEMBANGAN PACKAGING KRIPIK NENAS BERBASIS KEARIFAN LOKAL PADA KELOMPOK TANI TUGU MANDIRI KECAMATAN MEDANG KAMPAI KOTA DUMAI - Rispa Eliza; Bambang Suprapto; Nasrullah, Nasrullah; Muhammad Fazli (Komunitas Manajemen Kompetitif, 2025)
This community service program aims to enhance the capacity of local MSME actors in developing attractive, informative, and locally inspired packaging for pineapple chips products. The program was implemented with the Tugu Mandiri Farmers Group in Medang Kampai District, Dumai City, which has long faced challenges in packaging design and product identity. Using a participatory approach, the activities included observation, training, mentoring, and evaluation, allowing participants to engage directly in creating packaging designs that reflect local Malay cultural elements and regional color identities. The results showed significant improvement in participants’ understanding and skills in producing visually appealing and marketable packaging. The final product, branded “Keripik Nenas”, represents local innovation ready to compete in regional markets. Overall, this program strengthened awareness of innovation, professionalism, and cultural identity in business practices while promoting Dumai City as a center of creative, culturally based local industries